2014
DOI: 10.1111/ppl.12225
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis AtSUC2 and AtSUC4, encoding sucrose transporters, are required for abiotic stress tolerance in an ABA‐dependent pathway

Abstract: Sucrose transporters (SUCs or SUTs) play a central role, as they orchestrate sucrose allocation both intracellularly and at the whole plant level. Previously, we found AtSUC4 mutants changing sucrose distribution under drought and salt stresses. Here, we systematically examined the role of Arabidopsis AtSUC2 and AtSUC4 in response to abiotic stress. The results showed significant induction of AtSUC2 and AtSUC4 in salt, osmotic, low temperature and exogenous abscisic acid (ABA) treatments by public microarray d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 81 publications
4
95
0
2
Order By: Relevance
“…Several other results provide evidence that leaf Suc transporter gene expression is tuned by water deficit (Fig. 10), as in grapevine (Medici et al, 2014), rice (Oryza sativa; Ibraheem et al, 2011), and Arabidopsis (Gong et al, 2015). As source strength is defined as the ability to export sugar to sinks, our data demonstrate that the leaves of WD plants were a stronger source when the data were weighted by leaf mass.…”
Section: In Leaves Water Deficit Triggered Higher Sugar Content Whimentioning
confidence: 58%
“…Several other results provide evidence that leaf Suc transporter gene expression is tuned by water deficit (Fig. 10), as in grapevine (Medici et al, 2014), rice (Oryza sativa; Ibraheem et al, 2011), and Arabidopsis (Gong et al, 2015). As source strength is defined as the ability to export sugar to sinks, our data demonstrate that the leaves of WD plants were a stronger source when the data were weighted by leaf mass.…”
Section: In Leaves Water Deficit Triggered Higher Sugar Content Whimentioning
confidence: 58%
“…In silico analyses of the promoter regions of SUTs in Arabidopsis and rice showed that these regions contained LT response elements and other stress response elements, indicating that SUT might be regulated by cold temperatures (Ibraheem et al 2010). Recently, Gong et al (2015) reported that AtSUC2 and AtSUC4 were induced by cold and loss-of-function mutations resulted in hypersensitive responses to abiotic stress. Additionally, most cold-induced transporters are positively correlated with plant cold tolerance via the modulation of sugar allocation, such as MfINT-like (Sambe et al 2015), BvIMP (ERD6-like) (Klemens et al 2013b) and AtTMTs (Schulze et al 2012;Wormit et al 2006), suggesting that the up-regulated genes in the tea plant could exhibit similar functions as their homologous genes.…”
Section: Sugar Transporters Mediate Sugar Allocation In Response To Cmentioning
confidence: 98%
“…Because sucrose metabolism is distributed universally, wide association of sucrose transporter with other traits is predicted Gong et al 2015). For example, Li et al (2011) identified sucrose transporter alleles in Brassica napus that significantly correlated with seed yield traits, including number of effective branches, siliques per plant, and seed weight.…”
Section: Plant Growth Regulmentioning
confidence: 99%